The first fossil pycnocheiridiine pseudoscorpion (Pseudoscorpiones: Cheiridiidae: Procheiridium gen. nov.) from Cretaceous Burmese amber - Porta, Andrés O.; Michalik, Peter; Franchi, Ezequiel; Proud, Daniel N. (Zootaxa, 2020)
Procheiridium judsoni n. gen. et n. sp. is described from Burmese cretaceous amber. This species represents the earliest record of the pseudoscorpion subfamily Pycnocheiridiinae and the first fossil taxon of the subfamily to be recorded. The phylogenetic position of the new genus in the superfamily Cheiridioidea is discussed.